ON THE SPECIFIC STATE OF CRUSTAL STRESSES IN INTRACONTINENTAL OROGENS - Yu. L. Rebetsky (Геодинамика и тектонофизика, 2015)
The article presents a systematic review of the available tectonophysical data on the state of crustal uplifts and basins in intracontinental orogens. Based on results of the tectonophysical analysis of data on earthquake focal mechanisms for the Altai-Sayan and Northern Tien Shan regions, it is established that in many cases the crust in the basins and uplifts has antipodal structures, considering various types of the state of stresses. In the crust of the uplifts, maximum compression axes are usually sub-horizontal; in the crust of the basins, only the axis of the principal stress of minimum compression (i.e. maximum deviatoric extension) is sub-horizontal. These observations correlate well with estimations of deformations on the surface of the crust on the basis of the GPS-geodesy data, as well as with stress measurements taken directly on mining sites. The antipodal structures and physical fields in the crust of the uplifts and basins are not a random phenomenon. This suggests a common mechanism of deformation at the stage of active formation of the uplifts and basins. However, results of a similar tectonophysical analysis performed for the crust of the Pamir plateau and Tibet show that minimum compression stresses are subhorizontal in these regions, and the geodynamic type of the state of stresses is determined as horizontal extension or horizontal shearing. This pattern contrasts sharply with the type of the state of stresses of horizontal compression in the crust of the mountain ranges around the plateau (the Himalayas, Kunlun, Tsilian Shan, Hindu Kush), as well as with the state of stresses of active orogenic structures of the Tien Shan and Altai-Sayan regions.Based on the stress values estimated for a range of geodynamic types of the state of stresses, it is estimated that additional compression stresses of the order of 5.4 kbar are required for the transition from horizontal extension to horizontal compression. If the regional strain rates currently recorded by the GPS-geodesy are taken into account, such additional stresses need to be applied for about 10 million years to fulfill the transition.